New species of Capronia (Herpotrichiellaceae, Ascomycota) from Patagonian forests, Argentina - Sanchez, Romina Magali (2019)
Three new species belonging to Capronia are described from plants native to the Andean Patagonian forests, Argentina. The first record of C. chlorospora in South America is also reported. The identity of the three new species is based on detailed morpho-anatomical observations as well as analyses of ITS and LSU nuclear rDNA. A key to the Capronia species present in Argentina is provided.